2016
DOI: 10.1111/aor.12672
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of the Platelet Activity State Assay for the In Vitro Quantification of Platelet Activation in Blood Recirculating Devices for Extracorporeal Circulation

Abstract: Abstract:We designed an experimental setup to characterize the thrombogenic potential associated with blood recirculating devices (BRDs) used in extracorporeal circulation (ECC). Our methodology relies on in vitro flow loop platelet recirculation experiments combined with the modified-prothrombinase platelet activity state (PAS) assay to quantify the bulk thrombin production rate of circulated platelets, which correlates to the platelet activation (PA) level. The method was applied to a commercial neonatal hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Over the last few years, the PAS assay has been utilized extensively for in vitro pre‐clinical studies of device‐associated SMPA . However, no studies have utilized the PAS assay for monitoring SMPA in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, the PAS assay has been utilized extensively for in vitro pre‐clinical studies of device‐associated SMPA . However, no studies have utilized the PAS assay for monitoring SMPA in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet activity state (PAS) assay is a unique assay that has been developed specifically to assess SMPA. In previous pre‐clinical studies, we reported that PAS assay is a sensitive tool to monitor in vitro the progression of SMPA over consecutive/cyclic exposure of platelets to haemodynamic hypershear stress patterns pertinent to mechanical blood therapeutic recirculating devices, such as prosthetic heart valves, blood oxygenators, LVADs, and the total artificial heart …”
Section: Introductionmentioning
confidence: 99%
“…In last few years, the PAS assay has been utilized extensively for in vitro studies of PA, characterizing devices and situations with a wide range of imposed shear stress (19,(52)(53)(54)(55)(56)(57)(58)(59), where the non-physiological blood flow patterns mediate the platelets response. The PAS assay has been exploited through three different approaches.…”
Section: Emerging Laboratory In Vitro Tests Of Platelet Activationmentioning
confidence: 99%
“…One of the primary endpoints of preclinical testing of blood contacting cardiovascular devices is to ensure adequate blood biocompatibility . Previously, flow cytometric assays to quantify activated ovine platelets have been reported and shown to be sensitive to blood pump complications and when there was subsequent evidence of thromboembolism .…”
mentioning
confidence: 99%